CARDIOVASCULAR INVOLVEMENT IN RHEUMATOID ARTHRITIS - Elif Berber Menekşe,; Ferhan Cantürk,; Gamze Alaylı, (Archives of Rheumatology, 2004)
Rheumatoid arthritis (RA) is a chronic, systemic and inflammatory joint disease. Cardiac involvement is common in RA. Although cardiac involvement is clinically silent, many studies revealed that the mortality rate was increased in RA and cardiovascular disease was the most common reason of mortality in RA. In this review cardiac involvement in RA and the pathogenesis of cardiovascular disease in RA were briefly summarized.